Analisis Sentimen untuk Riset Pasar Saham: (Sebuah Studi Bibliometrik) - Edi Irawan (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
Sentiment analysis has been widely utilized in stock market research. To provide a comprehensive overview of this field, a bibliometric analysis was conducted on 223 articles related to sentiment analysis in the stock market published between 2010 and 2025 and retrieved from the Web of Science database. Specifically, this study identified active affiliations, countries or regions, publication sources, and research fields; traced the most cited articles; mapped scientific collaborations among authors, institutions, and countries or regions; and revealed the main research topics. The results indicate that journals in the field of computer science play an active role in publishing sentiment analysis-based stock market research. This study also highlights researchers from various geographic regions who have made significant contributions. Furthermore, the level of collaboration within a single region is higher than collaboration across regions. These findings are expected to provide an overview of the current state of research for researchers and practitioners, as well as help them understand the limitations of research when designing studies related to the application of sentiment analysis in the stock market.